2016
DOI: 10.4158/ep161435.gl
|View full text |Cite
|
Sign up to set email alerts
|

American Association of Clinical Endocrinologists and American College of Endocrinology Clinical Practice Guidelines for the Diagnosis and Treatment of Postmenopausal Osteoporosis — 2016

Abstract: A complete list of the Reviewers of the AACE/ACE Postmenopausal Osteoporosis Clinical Practice Guidelines can be found in the Acknowledgment. The American Association of Clinical Endocrinologists/American College of Endocrinology Medical Guidelines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
430
0
52

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(486 citation statements)
references
References 289 publications
4
430
0
52
Order By: Relevance
“…(1)(2)(3) In the setting of this uncertainty, the timely article by Cummings and colleagues in the current issue of JBMR, in which they present a post hoc analysis of their randomized placebocontrolled FREEDOM Trial, should have an immediate clinical impact. (4) In this report, Cummings and colleagues compare the rates of new or worsening vertebral fractures in postmenopausal osteoporotic women who discontinued denosumab with those who discontinued placebo.…”
mentioning
confidence: 99%
“…(1)(2)(3) In the setting of this uncertainty, the timely article by Cummings and colleagues in the current issue of JBMR, in which they present a post hoc analysis of their randomized placebocontrolled FREEDOM Trial, should have an immediate clinical impact. (4) In this report, Cummings and colleagues compare the rates of new or worsening vertebral fractures in postmenopausal osteoporotic women who discontinued denosumab with those who discontinued placebo.…”
mentioning
confidence: 99%
“…Even in glucorticoid-induced osteoporosis, for which a study [35] showed fewer fractures in patients treated with teriparatide than with alendronate, the American College of Rheumatology still recommends oral bisphosphonates. Despite this, a case Endocrinologists [36]. Increasing bone mass and improving microarchitecture with an anabolic drug before starting a bisphosphonate might change the risk for fracture when the patient is assessed after 5 years of anti-resorptive therapy.…”
Section: Avoiding Aff By Optimization Of Long Term Osteoporosis Managmentioning
confidence: 99%
“…Consequently, various groups have recommended limiting the use of HRT in postmenopausal women at risk of facture and women younger than 60 years or within 10 years of menopause (19). Alternatives to estrogen for the treatment of postmenopausal osteoporosis as recommended by the U.S. Food and Drug Administration (FDA) include bisphosphonates, raloxifene, calcitonin and denosumab; however, these drugs have been reported to exert drug-specific adverse effects (20). In turn, lifestyle modifications have been undertaken, such as changes in exercise and diet.…”
Section: Introductionmentioning
confidence: 99%